Phenotypic Characterization of Local Chickens in West Africa: Systematic Review - (:unkn) unknown (My University, 2022)
This review analyzes the processes of phenotypic and morpho-biometric characterization of West African local chicken. Data were collected on a set of 44 articles, and other reference documents were used to analyze and discuss the data collected. Existing studies on the phenotypic and molecular characterization of local chicken populations in West Africa indicate the presence of a wide variety of plumage colors and conformations, and intra-population genetic diversity. However, none of these studies have been able to identify the existence of a differentiated subpopulation that can be assimilated into a distinct race. The conclusions of this studies are not sufficient to ensure the non-existence of “race” in West Africa because many of these studies focus only on the phenotypic aspect, while molecular characterization makes it possible to identify differentiated populations with certainty. Additionally, the populations studied are often small in size, though remaining within the FAO recommendation standards. The spatial distribution used to compare the subpopulations was based on agroecological zones with strong interconnections to and shared with West African human populations, to the detriment of socio-cultural realities. In order to be more effective and conclusive, characterization work could consider the spatial distance of subpopulations in a comparison and the levels of exchange between the human communities from which these chicken subpopulations originate.
Keywords: African Research